A META ANALYTIC REVIEW ON ENTREPRENEURSHIP EDUCATION OF UNIVERSITAS CIPUTRA SURABAYA - Indudewi, Yuanita Ratna; Teofilus; Arifin, Darma Fathurahman; Nuradhi, Laurensia Maureen (International Business Management - Universitas Ciputra, 2023)
Universitas Ciputra Surabaya has been known for its Entrepreneurship Education since 2006, and many institutions came to do a benchmark study. More institutions came to Universitas Ciputra Surabaya during the pandemic for requisite entrepreneurship education modules and training. However, articles show conflicting evidence that entrepreneurship education cannot intensify entrepreneurial intention, which leads to a lack of entrepreneurial behavior. Extremely, a journal provided data that entrepreneurship education within several colleges and universities holds little to no responsibility in increasing the entrepreneurial rate among college graduates. This evidence comes from a different context and setting apart from Entrepreneurship Education Curricula developed over the years by Universitas Ciputra Surabaya academics. Of about 58 articles in the journal of entrepreneurship education published by Universitas Ciputra Surabaya academics, 14 articles correlated to entrepreneurial intention. Those 14 articles were processed using meta-analysis. The value of r2 = 0.354 indicates that entrepreneurship education has a very strong influence on entrepreneurial intention. Egger’s test results showed no publication bias within this research. The findings contribute to elevating the efficacy of the stakeholder of Universitas Ciputra Surabaya, especially now that “Program Merdeka Belajar” gives access to a broader community